HARUN NASUTION ISLAMIC EDUCATION THINKING: POSTGRADUATE PRESENTATION IN RELIGIOUS COLLEGE - Suryadi, Ahmad; Qamar, Syamsul (International Journal of Islamic Studies, 2021)
The objectives of this study are: (1) To determine the biography of Harun Nasution (2) To find out the efforts made by Harun Nasution in presenting postgraduate degrees in religious colleges. Harun Nasution is one of the reformers of Islamic education in Indonesia, he comes from Mandailing Natal, North Sumatra. According to Harun Nasution, the effort to present Postgraduate degrees in the scope of IAIN aims to produce scholars who are the driving force for education, research and development of science within the IAIN.